2020
DOI: 10.1002/ajpa.24106
|View full text |Cite
|
Sign up to set email alerts
|

Enamel thickness variation in the deciduous dentition of extant large‐bodied hominoids

Abstract: Objectives: Enamel thickness features prominently in hominoid evolutionary studies. To date, however, studies of enamel thickness in humans, great apes, and their fossil relatives have focused on the permanent molar row. Comparatively little research effort has been devoted to tissue proportions within deciduous teeth. Here we attempt to fill this gap by documenting enamel thickness variation in the deciduous dentition of extant large-bodied hominoids. Materials and methods: We used microcomputed tomography to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…One study observed that there is a difference in the pattern of tooth enamel distribution and thickness in deciduous molars of hominoids when compared to the pattern described for permanent molars. 28 Due to the scarcity of studies evaluating enamel in deciduous teeth, the authors have chosen to present the results of mean and standard deviation to serve as a parameter for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…One study observed that there is a difference in the pattern of tooth enamel distribution and thickness in deciduous molars of hominoids when compared to the pattern described for permanent molars. 28 Due to the scarcity of studies evaluating enamel in deciduous teeth, the authors have chosen to present the results of mean and standard deviation to serve as a parameter for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved using digital techniques and 3D reconstructions. The aforementioned important features are used today in a variety of studies, in evolutionary research, taxonomical assessments, and morphological studies [21,25,26], representing, in some cases, methodological extensions of techniques proposed for studies on real teeth [27]. The combination of enamel thickness measurements with other techniques, e.g., geometric morphometrics, is also characteristic for current odontological studies [28].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in enamel thickness in the deciduous dentitions of hominoids (H. sapiens, Pan troglodytes, Gorilla and Pongo) have recently been explored. 5 The thickness of dental enamel may act as a proxy for the durability of a tooth and reflect dietary preferences and possibly the lifespan. The varying patterns of wear and of enamel thickness correlates with dietary preferences and can act as a proxy for different diets.…”
mentioning
confidence: 99%